Polyarteritis Nodosa Renal Crisis with Malignant Hypertension (Global Journal of Medical Research, 2016)
A case of 28 years female with no significant past medical history presented with malignant hypertension. She was found to have Polyarteritis nodosa involving the kidney on angiography. She was treated successfully with steroids and cytotoxic drugs and made uneventful recovery. Her kidney function remained stable and her BP was controlled on Po medications. Even though she was negative for hepatitis B infection, the association was strongly confirmed in about 10% of patients. PAN should be suspected in any patients with multisystem involvement with hypertension and minimal findings in urinalysis. Polyneuropathy and high ESR are also red flags for PAN.